In search of the ox... : Gateways to understanding human individuation through guidance - Valencia Bolaños, Mónica E. (2012)
This paper summarizes several theoretical practices to one of the most important personal decisions in every human being, the path of self-knowledge. As long as those intrinsic needs arise, modern man is finding that the satisfaction of material needs, finally is neither happiness nor true peace. At this imaginary, the counselor's role is the ability to guide based on principles and values that ensure that path is found, since his great commitment is precisely accompany the discovery of talents and potential of people to get his genius and innate forms of normal growth to happiness and harmony. Among the ways there are those who were studied by a number of theoretical experts in human existence as Ortega y Gasset, Sabater, Jung, Heidegger, Gadamer, Luckmann, Habermas, Bauman, Binswanger. It is a fascinating tour of such analyzers, that motivate and specially challenge.